2013
DOI: 10.1002/jcp.24327
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ‐induced PI 3 kinase‐dependent Mnk‐1 activation is necessary for Ser‐209 phosphorylation of eIF4E and mesangial cell hypertrophy

Abstract: Transforming growth factorβ (TGFβ)-induced canonical signal transduction is involved in glomerular mesangial cell hypertrophy; however, the role played by the noncanonical TGFβ signaling remains largely unexplored. TGFβ time-dependently stimulated eIF4E phosphorylation at Ser-209 concomitant with enhanced phosphorylation of Erk1/2 (extracellular signal regulated kinase1/2) and MEK (mitogen-activated and extracellular signal-regulated kinase kinase) in mesangial cells. Inhibition of Erk1/2 by MEK inhibitor or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…S6A). We also determined the mesangial cell hypertrophy by the ratio of total protein content to the cell number [6, 18, 20]. Expression of miR-26a alone significantly induced mesangial cell hypertrophy analogous to high glucose treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S6A). We also determined the mesangial cell hypertrophy by the ratio of total protein content to the cell number [6, 18, 20]. Expression of miR-26a alone significantly induced mesangial cell hypertrophy analogous to high glucose treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Protein synthesis was measured by 35 S-methionine incorporation as described [18, 20]. Hypertrophy of mesangial cells was determined by the ratio of total protein to cell number as described previously [5, 18, 20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that inhibiting Mnks may reduce the eIF4F assembly. Another recent study also suggested that the dissociation of 4E-BP1 is highly dependent on the Mnk1-mediated eIF4E phosphorylation (Das et al, 2013). The dephosphorylation of 4E-BP1 by MNKI-19 could be also due to the Pim-1 inhibition as shown in the kinase assay.…”
Section: Mapk-interacting Kinase Inhibition In Amlmentioning
confidence: 97%
“…Phosphorylation of eIF4E reduces its affinity for the cap structure (16,17). There are numerous studies showing positive correlations between eIF4E phosphorylation and increased protein synthesis (18), cell cycle progression (19), cell proliferation (19,20), tumorigenesis (21)(22)(23), cell hypertrophy (24), transformation (25), and metastasis (26) (also reviewed in Ref. 27).…”
mentioning
confidence: 99%